VISUALISASI METODE SEQUENTIAL SEARCH - Dadang Haryanto; Akik Hidayat (JUTEKIN (Jurnal Teknik Informatika), 2014)
What is meant by Searching the programming technique isused to findatraceof databy way ofdatastorage. Thestorage spacecanbe an array in memory o rinafileon theexternal storage.Sequential Search is searchthrough multiple iterations from1up to the amountof data. Ateachrepetition, the data compared to the sought-i. If thesame, meaningthe datahas beenfound. In contrastto the endifthere is norepetition ofthe same data, meaningthe datadoes notexist. In theworst case, forNdata elements should beNtimesas manysearchesas well.Expected by theapplication of sequential visualization methods for thesearchengines this data can help how the workings of thesearch processto use yourdata by sequential searchmethods.Keyword: Programming, Visualization, Search